Correlates of Physical Activity among Adults with Sight Loss in High-Income-Countries: A Systematic Review - Rosie K. Lindsay (MDPI AG, 2021)
Background: Physical activity (PA) is essential for almost all facets of health; however, research suggests that PA levels among populations with sight loss are critically low. The aim of this review was to identify the correlates of PA among people with sight loss in high income countries, to inform future interventions and policies. Methods: MEDLINE, Web of Science, PsycINFO, SPORTDiscus, The British Journal of Visual Impairment, The Journal of Visual Impairment and grey literature were searched for studies which reported correlates of PA among adults with sight loss. The protocol is available from PROSPERO (CRD42020215596). Results: A total of 29 articles were eligible for review. Evidence from multiple studies reported that the vision impairment category, worse visual acuity, bilateral visual field loss, worse contrast sensitivity, those of the female gender, low self-efficacy, and environmental barriers were associated with lower levels of PA among populations with sight loss. Conclusions: Overall, correlates of PA among people with sight loss in high income countries are complex and vary across different population groups. Health professionals, eye care, and sight loss services should work together to identify people at risk of low PA, and provide a range of services and interventions to influence the modifiable factors that are associated with low PA.